[PP.30.17] KRILL OIL PHOSPHOLIPIDS IMPROVE LIPID PROFILE IN HYPERTENSIVE PERSONS. (September 2016) - Stojanov, V.; Radivojevic, N.; Marjanovic, M.; Lovic, D.
Abstract : Objective: The aim of this study was to assess the effectiveness of three-month treatment with krill oil phospholipids on lipid profile of persons with arterial hypertension. Design and method: The study comprised 159 persons with arterial hypertension (69 men and 90 women), aged 55.63 ± 10.84 years. All participants were given Krill Oil (500 mg capsules containing 225 mg krill phospholipids) for three months. Lipid status (total cholesterol, LDL-cholesterol, HDL-cholesterol and total triglycerides) was assessed with standard biochemical analysis at the beginning of the study and after three months of krill oil phospholipids therapy. Blood pressure was measured with standard oscillometric device. Regular antihypertensive therapy was not changed during the treatment. Results: Mean systolic blood pressure (SPB) at the beginning of the study was 134.12 ± 16.62 mmHg; mean diastolic blood pressure (DBP) was 81.49 ± 9.58 mmHg. After three months of therapy, mean SBP was similar 135.38 ± 16.86 mmHg, and DBP was similar 82.23 ± 9.56 mmHg. After krill oil phospholipids therapy, total cholesterol decreased from 6.43 to 6.02 mmol/L; the average LDL-cholesterol decreased from 4.09 to 3.76 mmol/L; the average triglycerides decreased from 2.56 to 2.15 mmol/L, whereas the average HDL-cholesterol significantly increased from 1.21 to 1.29 mmol/L. All changes were highly statistically significant. Conclusions: Three-month therapy with krill oil phospholipids significantly improves lipid profile in hypertensive persons.